Pendidikan Berbasis Hak Asasi Manusia dan Pengembangan Rintisan Sekolah Bertaraf Internasional pada Sekolah Menengah Atas - Penny Naluria Utami (Jurnal HAM, 2012)
The Constitution of the Republic of Indonesia in 1945 has mandated that one of the Indonesia's national goals is the creation of national intellectual life. Therefore every Indonesian citizens, regardless of their social status, race, ethnicity, religion, and gender are entitled to quality education services. One effort to improve the quality of education contained in Article 50 paragraph (3) of Law No. 20 Year 2003 on National Education System, which states that the central and or local government establish at least one unit of education at all levels of education to be developed as an international education unit. Article 12 of Law No. 39 Year 1999 on Human Rights states that everyone has the right to protection of personal development, to education, to educate themselves, and improve the quality of human life in order to be faithful, pious, noble responsibility, and welfare in accordance with human rights. The focus of this research is in accordance with the actual conditions covering: the utilization costs for the development of international school stubs (RSBI), the quality of student and teacher recruitment based on basic principles of human rights. This study uses a case study research design and conducted in North Sumatra and East Java.